Photogrammetry for concentrating solar collector form measurement, validated using a coordinate measuring machine - King, Peter; Sansom, Christopher L.; Comley, Paul (MDPI, 2019)
Concentrating solar power systems currently have a high capital cost when compared with other energy generating systems. The solar energy is captured in the form of thermal energy rather than direct electrical, which is attractive as thermal energy is more straightforward and currently more cost-effective to store in the amounts required for extended plant operation. It is also used directly as industrial process heat, including desalination and water purification. For the technology to compete against other generating systems, it is crucial to reduce the electrical energy cost to less than $0.10 per kilowatt-hour. One of the significant capital costs is the solar field, which contains the concentrators. Novel constructions and improvements to the durability and lifetime of the concentrators are required to reduce the cost of this field. This paper describes the development and validation of an inexpensive, highly portable photogrammetry technique, which has been used to measure the shape of large mirror facets for solar collectors. The accuracy of the technique has been validated to show a whole surface measurement capability of better than 100 mm using a large coordinate measuring machine. Qualification of facets of the MATS plant was performed during its installation phase, giving results of the shape, slope and intercept errors over each facet.
Keywords: parabolic trough; photogrammetry; validation; optimisation; CSP; solar collector